Immediate postpartum ultrasound evaluation for suspected retained placental tissue in patients undergoing manual removal of placenta. (September 2015) - Weissbach, T.; Haikin-Herzberger, E.; Bacci-Hugger, K.; Shechter-Maor, G.; Fejgin, M.; Biron-Shental, T.
Abstract: Objectives: Approximately 1% of term deliveries are complicated by retained products of conception. Untreated, this condition may cause bleeding, infection and intrauterine adhesions. This study assessed whether performing routine bedside uterine ultrasound immediately after manual removal of the placenta reduced the occurrence of undiagnosed, retained products of conception and its associated complications. Study design: A retrospective study was conducted using the records of patients who delivered and underwent manual removal of placenta at a single obstetrics center over a 6-year period. The outcomes of patients who were assessed using immediate bedside ultrasound were compared to a similar group who were treated based on clinical evaluation alone. All patients underwent ultrasound examination prior to discharge. Outcome variables included the rate of additional interventions (medical or surgical), abnormal pre-discharge uterine ultrasound findings, postpartum hemorrhage rate, puerperal fever and length of hospital stay. Results: A total of 399 charts were reviewed. Immediate post-procedural ultrasound was performed in 235 patients. The remaining 164 women did not undergo immediate post-procedural ultrasound. All patients underwent an ultrasound examination prior to discharge. Among the patients who had an immediate post-procedural ultrasound, 12 (5.1%) received immediate re-intervention (2 methergine, 6 curettage and 4 manual uterine revision) vs. no intervention in the second group ( p < 0.001). No statistically significant difference was found between the group of patients who had immediate post-procedural ultrasound and those who did not, in the rates of postpartum hemorrhage (3.1% vs. 0.7%, p = 0.13), abnormal ultrasound findings prior to discharge (14.9% vs. 14.8%, p = 0.96) or additional late intervention (7.2% vs. 7.9%, p = 0.79), respectively. Conclusions: Our findings suggest that immediate, bedside uterine ultrasound examination after manual removal of placenta might not change patient outcomes. Furthermore, it might increase unnecessary interventions. Further studies are needed to prospectively assess the benefit of routine uterine ultrasound examination after manual removal of placenta.